Major dietary patterns in relation to menstrual pain: a nested case control study - Nastaran Najafi; Hamidreza Khalkhali; Fatemeh Moghaddam Tabrizi; Rasoul Zarrin (BMC, 2018)
Abstract Background Dysmenorrhea is one of the most prevalent gynecological disorders, experienced by approximately two third of young women during menstruation. According to literature, nutrition can play a key role in the prevalence and severity of dysmenorrhea. This study aims to investigate the relation between dietary patterns and the risk of dysmenorrhea among university students. Methods A nested case control study was conducted among 293 students of Urmia University of Medical Sciences who were randomly recruited via a proportional cluster sampling method. From 293 students, 46 students with moderate to severe dysmenorrhea and 54 students without dysmenorrhea were assigned to the case and control groups, respectively. The major dietary patterns of students were identified by factor analysis and the association between dietary patterns and risk of dysmenorrhea was investigated using logistic regression analysis in SPSS 20. Results Three major dietary patterns were found and nominated as "Lacto-vegetarian", "Snacks" and "Mixed food items" patterns. After controlling for family history of dysmenorrhea, subjects in the second and third tertiles of "snacks" pattern had a 4.23 (95% CI = 1.32-13.58, P = 0.01) and 3.41 (95% CI = 1.10-10.50, P = 0.03) times, respectively, higher chance to experience moderate to severe dysmenorrhea in comparison with subjects in the first tertile. There was no significant association between the risk of dysmenorrhea and two other dietary patterns. Conclusions The results indicate that adherence to "snacks" pattern is associated with an increased risk of moderate to severe dysmenorrhea during menstruation among young women.